Identification and Determination of Flavonoids in Astragali Radix by High Performance Liquid Chromatography Coupled with DAD and ESI-MS Detection - Yu-Ling Wang; Lan-Fang Huang; Yun-Biao He; Xian-Zhen Xie; Wei Hu; Yan-Wen Lv (Molecules, 2011)
A method for the analysis of flavonoids in Astragali Radix by high-performance liquid chromatography (HPLC) combined with photodiode-array detection (DAD) and an electrospray ionization (ESI) - mass spectrometry (MS) was developed. After the samples were extracted with ethanol, the optimum separation conditions for these analytes were achieved using a gradient elution system and a 2.0 × 150 mm Shimadzu VP-ODS column. Eight flavonoids were identified to exist in Astragali Radix based on their characteristic UV data and mass spectra. The concentrations of three major components in this herb—ononin, calycosin and formononetin—were determined by LC/ESI-MS in positive selective ion monitoring (SIM) mode. The calibration curves were linear in the range of 0.9~180.0 μg·mL−1 for ononin, 1.8~360.0 μg·mL−1 for calycosin and 1.4~280 μg·mL−1 for formononetin, respectively. The limits of quantification (LOQ) and detection (LOD) were 0.9 μg· mL−1 and 0.2 μg mL−1 for ononin, 1.8 μg mL−1 and 0.5 μg·mL−1 for calycosin, 1.4 μg mL−1 and 0.5 μg·mL−1 for formononetin, respectively. The standard recoveries were between 95.4~104.7%. The developed method was proven to be useful for the quantitative and qualitative analysis of flavonoid constituents in various resources of Astragali Radix.